THE WARRIOR GOD AND THE PRINCE OF PEACE BIBLICAL PERSPECTIVES ON WAR AND PEACE - Kalluveettil, Paul (Journal of Dharma, 2002)
"With justice he judges and makes war. His eyes are like blazing fire, and on his head are many crowns .... He is dressed in a robe dipped in blood.... Out of his mouth comes a sharp sword with which to strike down the nations... He treads the winepress of the fury of the wrath of God Almighty." (Rev. 19:11-15)